Assessment of hazard on human health and aquatic life in acid mine drainage treated with novel technique. Issue 8 (17th November 2019) - Saha, Sukla; Saha, Priti; Sinha, Alok
ABSTRACT: The research investigates a novel method to treat acid mine drainage (AMD) using lime and sodium hydroxide modified fly ash (NCFA) with varied dose and time. The analysis showed that pH was raised to 8.24 and approximately 99% of Al, Cd, Cr, Cu, Ni, Pb; 97% of Co, Mn, Zn; 83% of Fe; 35% of Mg; 21% of Na, SO4 ; and 49% of Cl were removed after 20 min of reaction with 70 gm L −1 dose. The precipitation of these metals as well as sulfate in the form of gypsum on the NCFA surface was detected by X-ray diffraction and field emission scanning electron microscope. The possible mineral phases were identified by PHREEQC geochemical modeling. However, this analysis does not evaluate the hazard of the treated water to aquatic life and human health. Therefore, water quality index (WQI) and hazard index (HI) is proposed in this study to evaluate the risk and identify the optimum dose and time for AMD treatment. These indices confirmed that AMD should be treated with 70 gm L −1 dose of NCFA for 20 min to safeguard human and aquatic life. This study gives a new direction to treat AMD effectively and identify its potential risk to living organisms.